Prevalence and whole-genome analysis of multidrug-resistant Salmonella isolated from chicken carcasses in Hanoi - Nguyen, Trung Thanh; Le, Hoa Vinh; Ta, Yen Thi; Pham, Da Xuan; Nguyen, Nam Trung (Vietnam Journal of Biotechnology, 2022)
Salmonella enterica is one of the most dangerous food-borne pathogens posing a significant global concern especially to travelers returning from developing countries. Given that chicken is the main reservoir for Salmonella, the emergence and spread of multi-drug resistant Salmonella from chicken have not been fully described in Vietnam. The present study aimed to evaluate the phenotypic and genotypic antimicrobial resistances of Salmonella from chicken carcasses. Among 104 raw chickens collected from 5 districts in Hanoi city, 65 samples were contaminated with Salmonella of which the highest contamination rate was found in Thanh Xuan. A total of 63/65 (96.9%) of Salmonella isolates were resistant to at least one antibiotic and 61/65 (93.9%) of the isolates were found to be multidrug resistant. Whole-genome sequencing was employed to analyze 4 strains with high (12_S2 and 61_S18) and low (19_S4 and 8_S1) antimicrobial resistance patterns. Genomic analysis indicated the presence of 27 genes conferring antibiotic resistance. Genotypes were highly correlated to observed phenotypes in 4 strains. Importantly, extended-spectrum β-lactamase blaCTX-M-55 and colistin resistance mcr-3 were reported in isolates of Salmonella enterica serovar Typhimurium. This is the first report showing the prevalence and genome sequences of Salmonella from chicken carcasses collected in Hanoi, Vietnam. The results represented herein provided the basis to understand the dynamics of antibiotic resistance of Salmonella in Vietnam and to spot antimicrobial resistance determinants for early diagnosis.